Emission impact of pentanol on Pongamia biodiesel propelled diesel engine. Issue 1 (31st December 2022) - Prakash, S.; Sajin, J. B.; Ravikumar, J.
Abstract : The emissions characteristics of diesel-engine fuelled with different blends of Pongamia biodiesel i.e. PBD100, PBD90P10 (10% Vol of higher-alcohol dispersed in PBD100) and PBD80P20 (20% Vol higher-alcohol dispersed in PBD100) at 1800 rpm for compression ratio 16:1 were investigated. Results revealed that the NO x, HC, CO and smoke emissions were reduced with the increase in the concentration of pentanol. Further, PBD80P20 showed effective results when compared to diesel fuel.